2022
DOI: 10.1088/1402-4896/acab93
|View full text |Cite
|
Sign up to set email alerts
|

Carbon ion beam induced chemical modification and nano-pyramid growth on Si surface

Abstract: We report the growth of nano-ripple on, initially, smooth Si surface due to chemically guided additional instability generation during 10 keV C+ bombardment at grazing (700) ion incidence. Also, the transformation of the ripple structure to triangular nano-pyramidal structure at higher ion fluence is investigated in details. It is shown that the chemical nature of the surface changes due to silicon carbide formation at the ion impact sites, and the surface becomes a mixture of Si and SiC. The differential sput… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 40 publications
0
1
0
Order By: Relevance
“…A small portion of the implanted carbon reacts with the nitrogen present in the nano-template, which shows the CN peak in the C 1s spectra. The high-resolution Si 2p peak for C-implanted Si template with carbon ion-fluence 1 × 10 17 ions cm −2 , is fitted with four Gaussian-Lorentzian peaks positioned at 99.38 eV [19], 100.48 eV [20], 102.12 eV [19], and 103.14 eV [17,21], which corresponds to elemental silicon (Si), silicon carbide (SiC), silicon nitride (Si 3 N 4 ) and silicon oxide (SiO x ) respectively. The silicon nitride is formed during the 14 keV N 2 + ion-bombardment.…”
Section: Resultsmentioning
confidence: 99%
“…A small portion of the implanted carbon reacts with the nitrogen present in the nano-template, which shows the CN peak in the C 1s spectra. The high-resolution Si 2p peak for C-implanted Si template with carbon ion-fluence 1 × 10 17 ions cm −2 , is fitted with four Gaussian-Lorentzian peaks positioned at 99.38 eV [19], 100.48 eV [20], 102.12 eV [19], and 103.14 eV [17,21], which corresponds to elemental silicon (Si), silicon carbide (SiC), silicon nitride (Si 3 N 4 ) and silicon oxide (SiO x ) respectively. The silicon nitride is formed during the 14 keV N 2 + ion-bombardment.…”
Section: Resultsmentioning
confidence: 99%
“…Bhowmick et al investigated the relationship between the growth of nano ripples on a smooth Si surface and the chemical structure changes during C + bombardment. 24 They observed that the formation of silicon carbide at the ion impact sites changed the chemical nature of the surface, resulting in a mixture of Si and SiC. Differential sputtering of pure Si and SiC created additional instability, resulting in the appearance of ripple patterns on the surface.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is necessary to study the role of beam parameters based on the modification objectives and material properties. Bhowmick et al investigated the relationship between the growth of nano ripples on a smooth Si surface and the chemical structure changes during C + bombardment . They observed that the formation of silicon carbide at the ion impact sites changed the chemical nature of the surface, resulting in a mixture of Si and SiC.…”
Section: Introductionmentioning
confidence: 99%